“Jannat ki Talash” In a Romantic Sensual Context - Murtaza, Ali (sourcecoder, 2022)
Romanticism is the defining critical term of literature. Romantics usually see their future as a world shrouded in the mists of the past. When their dreams are shattered, they feel anguish and despair. This condition makes them suffer from torture, but they enjoy torturing themselves. Rahim Gul seems to reflect romanticism in his novel. In this novel, retrospectism, fantasyism, natural scenes and emotions are fully depicted. The novelist seems to highlight the richness of ideas and characters lost in dreams in his novel. So they feel happy even by taking refuge in the hidden valleys of the past. Therefore, all the qualities are found in his novel which is enough to prove this novel as romantic.